Hexa(methoxymethyl)melamine An Emerging Contaminant in German Rivers - Dsikowitzky, Larissa (Water environment research : a research publication of the Water Environment Federation, 2015)
Hexa(methoxymethyl)melamine (HMMM)-containing resins are used in the production of coatings and plastics for cans, coils, and automobiles. A previous study demonstrated that this compound was associated with acute toxic effects on daphnia. This study presents the first compiled data on the occurrence of HMMM as an emerging contaminant in German rivers. The compound occurred in 60 of 117 water samples from three river systems, with concentrations ranging between < 10 and 880 ng/L. Based on water concentrations and river flow on the day of sampling, the loads of HMMM were calculated for two rivers. The spatial distribution patterns of the loads showed large variations and did not follow clear trends along the stream course. These variations were attributed to effective removal processes, leading to sudden load decreases within short flow distances. The data suggest that HMMM could be discharged to the investigated rivers with wastewaters from the automotive industry and related branches